2015
DOI: 10.5455/aim.2015.23.374-378
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Research in Iran: a Scientometric Analysis of Publications Output During 2000-2014

Abstract: Aim:The aim of this study is to analyze the epilepsy research output of Iran in national and global contexts, as reflected in its publication output indexed in Scopus citation database during 2000-2014.Methods:This study was based on the publications of epilepsy research from Iranian authors retrieved Feb. 2015 from Scopus Citation database [www.scopus.com]. The string used to retrieve the data was developed using “epilepsy OR epilepsies” keywords in title, abstract and keywords and Iran in affiliation field w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…These 9 most productive Iranian universities have published 2,068 (86.20%) papers out of 2,399 papers in total. This finding is inconsistent with findings of Rasolabadi et al and the Biglu study ( 22 24 ). Though; these 9 Iranian universities are among the biggest domestic universities, with predictable productivity.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…These 9 most productive Iranian universities have published 2,068 (86.20%) papers out of 2,399 papers in total. This finding is inconsistent with findings of Rasolabadi et al and the Biglu study ( 22 24 ). Though; these 9 Iranian universities are among the biggest domestic universities, with predictable productivity.…”
Section: Discussioncontrasting
confidence: 96%
“…Iranian researchers have published their papers, mostly in domestic journals; the reason for this is that, most Iranian journals have only recently been qualified to be indexed by Scopus. In a study by Rasolabadi et al, there were 5 journals publishing 140 (20%), of which there was just one Iranian publication which became the first amongst other publications ( 22 ). Biglu in his study, found that most of the Iranian studies were issued in Thailand, the United States and the United Kingdom ( 23 ), which is not consistent with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Rasolabadi and his collogues 6 followed the footsteps of Gupta et al 4 and conducted a similar study in Iran.Their methodology was similar to the one used by Gupta et al, 4 including the use of Scoups as the only database. They included only 702 articles in their study over the period of 14 years with average citations per publication being 4.56.…”
Section: Discussionmentioning
confidence: 97%
“…In April of 2019, and in response to this situation, the LA regional chapter of the ILAE conducted capacity building sessions on scientific, social, and cultural issues in order to promote education and awareness about epilepsy and highlight the need to develop specialized treatment centers as well as advancing medical research [ 26 ]. Experiences of LMICs, like that of Iran, that show strengthening of scientific collaborations resulting in an progressive increase of scientific production with greater visibility and impact on epilepsy research demonstrate that building successful collaborations is not only feasible but key to improving output [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of this disease in LMICs as in LA, it is important to analyze scientific production trends. A bibliometric analysis is a method that allows to measure scientific productivity in multiple fields, such as type of document, geographical and institutional distribution, and citation rate [ 9 ]. Studies indicate that scientific production on epilepsy in Latin America can be rare, as has been shown by Park KM, et al.…”
Section: Introductionmentioning
confidence: 99%